Zoning Study on Influence Intensity of Cao'e River Sluice on River Network Drainage Based on 2D Numerical Model. Issue 1 (1st May 2022) - Yu, Junfeng; Chen, Weijin; Fang, Zhihao; Li, Dongfeng; Li, Zihao; Yang, Le
Abstract: Shaoxing City is located in the central and northern part of Zhejiang Province, generally showing the topographic trend of high in the South and high in the North. The South is mountainous and the North is plain. There are many rivers in the river network, which are staggered and complex. A two-dimensional mathematical model for flood control and drainage of river network in Shaoxing plain is established, the hydrodynamic influence of Cao'e River gate on river network in different regions is studied, and the characteristics of each region are analyzed. According to the zoning of the impact intensity of Cao'e River sluice on river network hydrodynamic force, six obvious zoning from strong to weak are obtained, and the characteristics of each region are analyzed. It has reference value for comprehensively formulating sluice dispatching operation procedures, changing river network hydrodynamic force distribution and other non-engineering countermeasures, and provides decision-making basis for river network comprehensive management and hydrodynamic force utilization.